Assessing Reading Strategy Training Based on CALLA Model in EFL and ESL Context - Karbalaei, Alireza (Íkala, Revista de Lenguaje y Cultura, 2011)
Reading strategies instruction is currently gaining much attention as an effective means of enhancing reading comprehension. In this research, we examined the effect of Underlining Strategy Intervention, based on the CALLA model in EFL and ESL contexts. A group of 189 college students were randomly selected from different universities in Iran and India. Based on a proficiency test, students were grouped into high, moderate, and low level. Then, the underlining strategy was taught during the treatment sessions. The results suggest that intervention or explicit instruction was effective in increasing the reading comprehension of both Iranian and Indian students although Indian ESL students were able to perform better in comparison to their Iranian EFL counterparts. There was no significant difference between proficiency level and students' performance in reading comprehension in EFL and ESL contexts. In addition, there was no significant difference between males and females in both contexts.